Building a peace economy? : Liberal peacebuilding and the development-security industry - Peterson, Jenny H. (Book collections on Project MUSE., 2014)
This study critically examines the range of policies and programmes that attempt to manage economic activity that contributes to political violence. Beginning with an overview of over a dozen policies aimed at transforming these activities into economic relationships which support peace, not war, the book then offers a sustained critique of the reasons for limited success in this policy field.